Surgical Techniques for Tricuspid Valve Disease - Belluschi, Igor; Del Forno, Benedetto; Lapenna, Elisabetta; Nisi, Teodora; Iaci, Giuseppe; Ferrara, David; Castiglioni, Alessandro; Alfieri, Ottavio; De Bonis, Michele (Frontiers in Cardiovascular Medicine, 2018)
Tricuspid valve disease affects millions of patients worldwide. It has always been considered less relevant than the left-side valves of the heart, but this “forgotten valve” still represents a great challenge for the cardiac surgeons, especially in the most difficult symptomatic scenarios. In this review we analyze the wide spectrum of surgical techniques for the treatment of a diseased tricuspid valve.